African American dramatists : an A-to-Z guide - Nelson, Emmanuel S. (Emmanuel Sampath), 1954- (Greenwood Press, 2004)
"African American playwrights have received less critical attention than poets and novelists. This reference offers thorough critical assessments of more than 60 African American dramatists from the 19th century to the present." "Each entry is written by an expert contributor and provides a biography, a discussion of major works and themes, a survey of the dramatist's critical reception, and primary and secondary bibliographies. The volume closes with a selected, general bibliography."--Jacket